Cerebral carbon dioxide embolism after kidney cancer laparoscopic surgery with full neurological recovery: A case report. Issue 27 (2nd July 2020) - Li, Yuan; Zhang, Enlong; Yuan, Huishu
Abstract: Rationale: Cerebral carbon dioxide embolism (CCDE) is a rare cause of stroke and is a recognized life-threatening complication.CCDE may result from direct intravascular CO2 insufflation during surgery. Due to the lack of typical clinical manifestations, the disease is often missed or mistaken for another condition. The clinical signs and symptoms depend on the speed and volume of embolized gas entering the blood and the patient's condition. In particular, patent foramen ovale has been found to be associated, in rare cases, with the intraoperative entry of gas into the arterial system. Patient concerns: In this report, we present the case of a 35-year-old woman with kidney cancer who underwent laparoscopic right partial nephrectomy. Diagnosis: After the laparoscopic surgery, the patient was initially diagnosed with acute cerebral infarction. Interventions: The patient was treated according to the standard method for treatment of acute cerebrovascular disease. Outcomes: Three days after the laparoscopic procedure, the patient gained consciousness, and she was discharged without any neurologic sequelae on postoperative day 12. Lessons subsections as per style: Due to the low incidence and sudden occurrence of CCDE, there is a strong likelihood of missed diagnosis or misdiagnosis, and it is; therefore, important to be aware of the risk. The findings from this report would be highly useful as a reference to clinicians in the future.